International Mobility of Students in Italy and the UK: Does It Pay off and for Whom? - Sylke V. Schnepf; Beatrice d'Hombres (Institute of Labor Economics (IZA), 2018)
International student mobility is the most recognised element of Erasmus+, a major EU policy. Not enough is known about the causal effect of studying abroad on labour market outcomes. This is because most of the existing studies dismiss selection bias: the different composition of students opting and not opting for studying abroad. The purpose of this paper is to answer the following three questions, whilst accounting for selection bias. First, does international student mobility (ISM) have an effect on labour market outcomes? Second, do the returns to ISM vary between two countries with contrasting labour market and education systems? Third, do the returns to ISM differ according to the socio-economic background of the students? Results are compared between Italy and the UK using Italian Institute of National Statistics and UK Higher Education Statistics Agency graduate survey data. Using propensity score matching, the returns to study-related stays abroad are estimated on a set of labour market outcomes around six to twelve months and three years after graduation for undergraduates (UK and Italy) and postgraduates (Italy only). Results indicate that mobility is positively associated with some outcome variables under scrutiny. Mobile graduates seem to benefit from better employment chances than non-mobile graduates. Returns to ISM tend to be slightly higher among graduates in Italy. Mobility seems to matter most for uptake and completion of further post-graduate studies in Italy. It is the especially the socially disadvantaged mobile who opt for further education after graduation.
Keywords: I23; I24; I26; 330; international student mobility; mobility abroad; labour market outcomes; propensity score matching; Italy; UK